2018
DOI: 10.1111/mmi.14160
|View full text |Cite
|
Sign up to set email alerts
|

CLR‐4, a novel conserved transcription factor for cellulase gene expression in ascomycete fungi

Abstract: Fungal degradation of lignocellulosic biomass requires various (hemi-)cellulases and is an important part of the natural carbon cycle.Although induction of cellulases has been described for some saprobic filamentous fungi, the regulation of cellulase transcription is complex and many aspects are still poorly understood. Here, we identified and characterized the novel cellulase regulation factor NcCLR-4 in Neurospora crassa and its ortholog MtCLR-4 in Myceliophthora thermophila. Deletion of CLR-4 resulted in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 87 publications
0
33
0
Order By: Relevance
“…Similarly, Hxk1 of S. cerevisiae was highly transcribed in cellobiose-grown cells [7]. Mycth_2297364 also showed elevated transcript levels in cells grown with glucose, starch, and Avicel compared with cells grown in starvation conditions [26,34]. These data indicate that Mycth_2297364 is the predominant isoenzyme when cells are grown with fermentable carbon sources.…”
Section: Comparison Of Transcriptomes Of M Thermophila Wt Between Cementioning
confidence: 81%
See 2 more Smart Citations
“…Similarly, Hxk1 of S. cerevisiae was highly transcribed in cellobiose-grown cells [7]. Mycth_2297364 also showed elevated transcript levels in cells grown with glucose, starch, and Avicel compared with cells grown in starvation conditions [26,34]. These data indicate that Mycth_2297364 is the predominant isoenzyme when cells are grown with fermentable carbon sources.…”
Section: Comparison Of Transcriptomes Of M Thermophila Wt Between Cementioning
confidence: 81%
“…2d). In previous studies, two genes encoding intracellular β-glucosidases were also induced by Avicel [26] and plant biomass [35], indicating that they are the most relevant enzymes for converting cellobiose to glucose when M. thermophila is cultured with either cellobiose or plant-derived biomass as the sole carbon source.…”
Section: Comparison Of Transcriptomes Of M Thermophila Wt Between Cementioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the transcription factors CLR-1 and CLR-2 were essential for growth on cellulose in N. crassa (Coradetti et al, 2012). Recent studies have shown that the CLR-4 acted as a positive activator of cellulase expression by directly binding to the promoters of CLR-1 and CLR-2 (Liu et al, 2019). CLR-3 repressed the cellulolytic response through CLR-1 (Huberman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…qRT-PCR was performed as previously described (94). The actin gene NCU04173 was used as an endogenous control for N. crassa, and Mycth_2314852 was used as an endogenous control for M. thermophila.…”
Section: Plasmid Construction and Transformationmentioning
confidence: 99%